PROFIL GELATINISASI BEBERAPA FORMULASI TEPUNG-TEPUNGAN UNTUK PENDUGAAN SIFAT PEMASAKAN (GELATINISATION PROFILE OF SEVERAL FLOUR FORMULATIONS FOR ESTIMATING COOKING BEHAVIOUR) - Nelis Imanningsih (Persagi, 2012)
ABSTRACT The combination of starch from various sources, salt and protein, are the basic formulation often found in the Indonesian traditional food. The different composition of amylopectine-amylose and the interactions among the ingredients in the formulation, determines pasting properties in order gain a suitable texture characteristics. The aim of the research is to study the interactions of severals kinds of flours with water, white egg protein, and salt and its influences to the cooking behaviour of semi-solid food. There are four formulations for each kind of flour (rice, glutenniuos rice, wheat and cassava) that are: (1) water: flour = 25 : 3 g; (2) water : flour : salt = 25 : 3 : 0.28 g; (3) water : flour : albumen = 25 : 3 : 0.3 g; and (4) water : flour : salt : albumen = 25 : 3 : 0.28 : 0.3 g. The flours are analysed for proximate, particle size distribution and amylose-amylopectine composition. Pasting behaviour is measured using Rapid Visco Analizer (RVA) to determine peak viscosity, peak temperature, and peak time gelatinisation. Rice, glutinous rice, wheat and cassava flours have different gelatinization profiles that depend on starches structural origin and amylose and amylopectin composition. Wheat flour has the lowest peak viscosity among four type of flour examined, whether cassava flour has the highest. Salt in starch-water system delays peak time. Egg white protein raises peak viscosity of starches, the addition of salt and egg white protein simultaneously into the system increases peak viscosity and causes the peak occurs earlier. In food processing, tapioca flour can be used to give viscosity at short time cooking but it could not give a sufficient viscosity to the cold products. Rice flour needs a long time cooking to give a suitable viscosity to the products, however this viscosity can hold well in cold temperature. Keywords: flour, salt, protein, gelatinisation, viscosity ABSTRAK Kombinasi berbagai macam tepung dengan garam dan protein putih telur merupakan formulasi dasar yang banyak dijumpai pada makanan tradisional Indonesia. Komposisi amilopektin-amilosa yang berbeda serta adanya interaksi bahan di dalam formula sangat menentukan sifat pemasakan untuk mendapatkan karakteristik tekstur yang diinginkan. Untuk mempelajari interaksi beberapa jenis tepung dengan air, protein putih telur dan garam serta pengaruhnya terhadap sifat pemasakan makanan semi-solid. Ada empat formulasi untuk setiap jenis tepung (beras, beras ketan, terigu dan tapioka), yakni: (1) air : tepung = 25 : 3 g; (2) air : tepung : garam = 25 : 3 : 0,28 g; (3) air : tepung : protein putih telur = 25 : 3 : 0,3 g; dan (4) air, tepung, garam, protein putih telur = 25 : 3 : 0,28 : 0,3 g. Tepung-tepungan dianalisis kandungan proksimat, distribusi ukuran partikel dan komposisi amilosa-amilopektinnya. Sifat pemasakan diuji dengan menggunakan Rapid Visco Analizer (RVA) untuk menentukan viskositas, suhu dan waktu puncak terjadinya gelatinisasi. Tepung beras, beras ketan, terigu dan tapioka memiliki sifat gelatinisasi berbeda yang berhubungan dengan struktur pati dan komposisi amilosa-amilopektin. Tepung terigu memiliki viskositas puncak yang paling rendah, sementara tepung tapioka tertinggi. Adanya garam akan menunda waktu terjadinya gelatinisasi. Protein putih telur meningkatkan viskositas puncak, dan adanya garam dan protein putih telur secara bersamaan meningkatkan viskositas puncak dan menyebabkan viskositas puncak ini terjadi dengan lebih cepat. Dalam pengolahan pangan, tepung tapioka dapat digunakan untuk memberi kekentalan pada waktu pemasakan yang singkat, tetapi kurang dapat memberikan kekentalan yang cukup pada produk yang dingin. Tepung beras memerlukan waktu pemasakan yang cukup lama untuk memberikan kekentalan yang baik pada produk, tetapi kekentalan ini dapat bertahan baik pada suhu yang dingin. [Penel Gizi Makan 2012, 35(1): 13-22] Kata kunci: tepung, garam, protein, gelatinisasi, viskositas